Evaluation of the promising neighbourhoods community program to reduce health inequalities in youth: a protocol of a mixed-methods study - Mirte Boelens; Dafna A. Windhorst; Harrie Jonkman; Clemens M. H. Hosman; Hein Raat; Wilma Jansen (BMC, 2019)
Abstract Background Reducing socioeconomic health inequalities among youth is a major challenge for governments around the world and reports on successful attempts are scarce. Socioecological and integral approaches with collaborative partnerships and community engagement are recommended but knowledge about the effectiveness and effective and ineffective elements is limited. The Promising Neighbourhoods program employs such an approach aiming to reduce socioeconomic inequalities in health, safety and talent development in youth. We will evaluate the process-implementation, and effectiveness of the Promising Neighbourhoods program. Methods/design Core elements of Promising Neighbourhoods are a collaborative community programming approach with stakeholders, data-based priority setting, knowledge-, and theory-based policies and evidence-based interventions. Community stakeholders and key-leaders from the neighbourhoods are engaged in the program. For this evaluation study the program will be implemented in three intervention neighbourhoods. These neighbourhoods will be compared to three control neighbourhoods at baseline in 2018/2019 and at follow-up in 2020/2021 after full implementation of the Promising Neighbourhoods program. Intervention neighbourhoods receive a tailored intervention-package including evidence-based interventions and additional measures by community stakeholders. In control neighbourhoods, no special planning will take place thus interventions are offered as usual. A mixed-methods approach following the stages of the logic model from program is applied for this evaluation. Questionnaires, focus groups, and registration data will be collected among community stakeholders, key-leaders, and youth to evaluate the process-implementation of the program. Indicators of intermediate and ultimate outcomes will be studied among N = 818 children and N = 818 youngsters using difference-in-difference regression analysis to evaluate the effectiveness of the Promising Neighbourhoods program. Discussion Hypotheses are that a collaborative community approach with stakeholders leads to clear priority-setting and better tailored interventions of better quality. We further hypothesise a decline in socioeconomic inequalities in intermediate and ultimate outcomes for health, safety and talent development in the intervention neighbourhoods in comparison to control neighbourhoods. The results add knowledge about effective and ineffective elements of collaborative community programming approaches to reduce health inequalities in youth and thus are relevant for local and national public health authorities. Trial registration Netherlands National Trial Register number NL7279. Date of registration: 26-Sept-2018.